Analyses in the economics of aging - Wise, David A. (University of Chicago Press, 2005)
"Analyses in the Economics of Aging presents a massive amount of new research on several popular and less-examined topics pertaining to the relationship between economics and aging. Among the many themes explored in this volume, considerable attention is given to new research on retirement savings, the cost and efficiency of medical resources, and the predictors of health events." "Carefully compiled and containing some of the most cutting-edge research and analysis available, this volume should be of interest to any specialist or policymaker concerned with ongoing changes in savings and retirement behaviors."--BOOK JACKET.